Body dissatisfaction and its relationship with overweight, sedentary behavior and physical activity in survivors of breast cancer - Ribeiro, Fernanda E. [UNESP] (2018)
Objectives: This study aimed to verify the prevalence of body satisfaction in breast cancer survivors and the association of this variable with overweight, sedentary behavior and physical activity in this population. Study Design: This is a cross-sectional study realized in Presidente Prudente–Brazil. Breast cancer survivors participated in this study. Questionnaires were used to obtain data on socioeconomic status, body dissatisfaction, sedentary behavior and level of physical activity. The association between body dissatisfaction and the independent variables was verified through binary logistic regression in the unadjusted model and model adjusted by socioeconomic level. Results: A total of 102 breast cancer survivors participated in this study with a mean age of 58.2 (±10.3) years. The prevalence of body dissatisfaction was 75.7%. Body dissatisfaction was higher in women with higher BMI (pvalue = 0.003) and in woman with high sedentary behavior (p-value = 0.049). Women with overweight had 7.87 times more chance of presenting body dissatisfaction. Women who reported hormone therapy were approximately 3 times more likely to be dissatisfacted with their body. Conclusion: Body dissatisfaction was associated with lower age, high sedentary behavior and overweight in breast cancer survivors in the unadjusted analysis. When adjusted for socioeconomic status, only the variables of overweight and hormone therapy were associated with body dissatisfaction.